2020
DOI: 10.11114/ijsss.v8i3.4779
|View full text |Cite
|
Sign up to set email alerts
|

Young Age and Crime in Society: A Study on Youth Prisoners in Bangladesh

Abstract: In a given society, crime is a social phenomenon and an inconsistent act of social order. Engagement of young boys and girls in diverse criminal activities is becoming a universal and more complicated issue in human society. The involvement of youths in different types of crimes is also becoming a major concern in Bangladesh. Hence, this study aimed to investigate the factors influencing the young prisoners in the involvement of various criminal activities. The major theoretical perspectives of criminology, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The researchers summarized the transcribed data by using condensation and categorized those into a different theme. To gather data, researchers also used secondary sources like articles, journals, reports, books, websites and, dissertations etcetera (Haque, Haque, & Muniruzzaman, 2020). After collecting all the data from primary and secondary sources, researchers interpreted the result by working out the implications of the collected data, after that reported the research findings.…”
Section: Methodsmentioning
confidence: 99%
“…The researchers summarized the transcribed data by using condensation and categorized those into a different theme. To gather data, researchers also used secondary sources like articles, journals, reports, books, websites and, dissertations etcetera (Haque, Haque, & Muniruzzaman, 2020). After collecting all the data from primary and secondary sources, researchers interpreted the result by working out the implications of the collected data, after that reported the research findings.…”
Section: Methodsmentioning
confidence: 99%
“…Masa remaja yang selalu ingin mencoba-coba sesuatu yang baru inilah yang membuat remaja rentan memiliki keinginan untuk berbuat kriminal (Muntasir Maruf, Rahman, Rahman Khan, & Jahan, 2017). Selain itu, faktor ekonomi dan kemiskinan dapat menjadi penyebab remaja menjadi dekat dengan dengan aksi kriminalisasi karena tidak mampu untuk memenuhi kebutuhan hidup (Halsey & Deegan, 2015;Haque, Haque, & Muniruzzaman, 2020). Perkembangan zaman dan kemajuan teknologi yang tidak dapat dimanfaatkan dengan baik juga tidak memengaruhi remaja untuk berbuat kriminal (Basto-Pereira, Miranda, Ribeiro, & Maia, 2016).…”
Section: Pendahuluanunclassified
“…Regarding the type of family where these teachers or clerics come from Egbon et al (2009) submitted that parents at homes and religious community leaders (teachers of religious studies) in schools failed to portray good practices of religious culture which hurt the religious teachings and practices among the students or youths in the society. Haque et al (2020) findings revealed that too many young clerics or teachers from broken families are prone to exploit their members or students to satisfy their unmet needs or desires through ungodly means. Rahman (2008) added that such act tends to put society into social chaos and violent crime.…”
Section: Commercialization Of Jalabi Among the Teachers' Of Islamic S...mentioning
confidence: 99%